Use of triple flat-type air coil inductive resonance as an oil palm fruit maturity sensor - Aliteh, Nor Aziana (2018)
Conventionally, a human inspector is used to inspect the ripeness of oil palm fresh fruit bunch (FFB) which can be inconsistent and inaccurate. There are various new methods that are proposed to grade the ripeness of the oil palm FFB such as spectroscopy imaging techniques. This research aims to improve the oil palm maturity detection inductive resonance method using triple series flat-type air coil. The first objective of this research is to design triple flat-type air coil for oil palm fruit maturity sensor. Besides that, the thesis also aimed to investigate the relationship between oil palm fruitlet sample resonance frequency and fruitlet capacitance against progressing week and moisture content. In addition, its effectiveness with single flat-type air coil configuration is compared in terms of sensitivity and precision in order to select the best triple series flat-type air coil among two types of coil series tested. The method used for oil palm fruit maturity detection in this study is inductive sensor concept based on a resonant frequency technique. From the resonant frequency value, the fruitlet capacitance is identified by subtracting the self-capacitance of the coil with the sample and without the sample. There are three types of evaluation used in this study, namely: direct ripeunripe, week, and moisture comparison. From these three evaluations, the differences between ripe and unripe were identified and compared. The sensitivity performance was assessed using the differences value and the precision was assessed by using the value of the coefficient of variation cv. Based from the results obtained, the peaks from inductance-frequency curve shifted closer to the peak curve of the air as the oil palm fruitlet ripens but the fruitlet capacitance decreased as the oil palm fruitlet matures due to the reduction of moisture content in the fruitlet. Depending on the coil configuration, the triple series technique was able to influence its sensitivity obtained in comparison to the single flat-type coil structure. The Triple I, a triple series coil with fixed number of turns N=200 with different length (3mm, 5mm, 10mm), showed better results than the Triple II coil with fix length l=5mm and different number of turns (N=140, 200, 400). Triple I and II also improved the sensitivity performance of its equivalent single coil by 353% and 63% respectively for 1st peak resonance frequency average differences. In addition, Triple I also proved to be more precise with small average coefficient of variation value for all three peaks (cv=0.2284) when compared to Triple II (cv=0.8401). In conclusion, the development of this sensor proves the capability of inductive elements such as coil to be used as a detection element to determine the ripening stages of the oil palm FFB sample.